Ethical Dilemmas Behind The Unsmoothed Framework Of The National Public Oversight Bodies - Marta TACHE; Ștefania-Florentina NEAGU; Ioana IGNAT (Communications of International Proceedings, 2023)
The aim of Public Oversight Bodies (POBs) is to improve firms’ audit quality through inspections of audit engagements. Nonetheless, the effectiveness of specific actions of POBs is yet to be documented in the literature. By using a hand-collected data on the framework of POB inspection framework from all the European countries, we are able to provide novel evidence that a smoothed framework of POB inspection can influence the appearance of ethical dilemmas in auditing. Specifically, after analyzing the general frame of the European POBs, we find that the setting of national POBs differs in time and the unsmoothed frame of POB inspections varies from country to country even if there are some recommendations developed by the European Directive 2014/56/EU and the Regulation 537/2014. Overall, this research documents that the uniform disclosure of annual reports is relevant for auditors and the effect of national POB inspections augments the audit quality.
Keywords: auditing; POB; inspections; ethical dilemmas; morality